(untitled) (DARYAFT, 2023)
Mustafa Karim is an epoch-making fiction writer of Urdu who, while maintaining the tradition of fiction, has also given new freshness to the eastern and western perspective of fiction. His fictions are excellent in terms of technical, artistic and thematic aspects, while the themes are East and West society, World War I and II, partition of India, migration problems, violence in religions, human tolerance, class division and psychology, problems of immigrants. , made the theme of sexual freedom and promiscuity. Most of his fiction depicts the life of immigrants and emigrants. Echoes of the past, consciousness and narrative style have been adopted in these legends. Every Short story is a manifestation of tragedy, sorrow, and suffering. This article gives a brief overview of his short stories.